Repetitive transforaminal steroid injections in cervical radiculopathy: a prospective outcome study including 140 patients - Persson, Liselotte; Anderberg, Leif (Evidence-Based Spine-Care Journal, 2012)
Study design: Prospective case series. Objective: To evaluate the effect of three repetitive transforaminal steroid injections in a large series of selected patients with cervical radiculopathy caused by spondylosis.Methods: Consecutively, 140 patients with long-lasting medical history, clinical findings, and MRI indicating a cervical nerve root origin based on degenerative disease and a positive selective transforaminal diagnostic nerve root blocks with local anesthetics resulting in at least 50% temporary arm pain reduction were included. Before treatment started, patients underwent a clinical examination by a neurosurgeon. All patients were followed-up and evaluated by one physiotherapist at the neurosurgery outpatient clinic. A designed outcome questionnaire including Neck Disability Index (NDI), Symptoms Frequency Index, and Visual Analog Scale for pain intensity were used. A series of three transforaminal steroid injections, with 3 weeks in between, were performed by a neuroradiologist using image intensifier guidance in an x-ray suite. At 12–14 weeks after the first injection, follow-up was performed. Criteria for positive response to the treatment was > 50% radicular arm pain reduction. Except for occasional painkillers, no other treatment was given to the patients.Results: Positive response to the treatment was achieved in 49% (n = 69) with a significant difference in NDI and pain intensity between responders and nonresponders.Conclusions: Repetitive transforaminal steroid injections may reduce symptoms (frequency, intensity, and fewer limitations of daily living activities) of radiculopathy in patients with degenerative disease in the cervical spine at a short time follow-up.The definiton of the different classes of evidence is available here.